Case analysis of the do-it-yourself industry. Issue 5 (9th November 2015) - Hatton-Jones, Siobhan; Teah, Min
Abstract : Purpose: – The purpose of this paper is to examine the accelerated growth within the Australian do-it-yourself (DIY) market and discusses the factors and drivers affecting consumer motivations to engage in such assembly tasks. Design/methodology/approach: – Using a case study approach, evaluations and critical analysis of the DIY industry was being formulated by drawing on real life brands and examples. An analysis of various DIY retail strategies and DIY decking companies was synthesised to provide insights into the DIY industry. Findings: – The insights into the industry outlines the changing consumer attitudes and motivations towards DIY and decking tasks. The findings on an evolving DIY industry, in particular the decking market demonstrate useful implications for academics, policy makers and brand practitioners. Originality/value: – There have been little industry studies that delve into specifically decking products. Considering the vast increase in homeware, renovations, and gardening, the study provides insights from various case studies into the strategies undertaken by Australian and global companies. In addition, the majority of studies undertaken have also been concerned with the intrinsic motivations of consumers and not necessarily the extrinsic effect that brands and retailers advertently and inadvertently communicate and signal to consumers of DIY products.